Pengaruh Kepemimpinan Kepala Madrasah dan Komitmen Guru Terhadap Efektifitas Madrasah di Lhokseumawe - Muhammad Fadhli (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2019)
This article aimed to determine: (1) the effect of Principal Leadership in Effectiveness Islamic School (2) the effect of Teacher Commitment in Effectiveness Islamic School. This article aimed to obtain the effect of exogenous variables on endogenous variables of research and this research use Path analysis. Subjects were principal and teacher in Lhokseumawe Islamic School. The sample was 108. Based on the hypothesis testing can be concluded: (1) there was a direct effect Principal Leadership to Islamic School Effectiveness by t count ρ31> t table α=5%(3,787> 1,659); (2) there was a direct effect Teacher Commitment to Islamic School Effectiveness by t count ρ32> t table α=5%(3,481> 1, 659). The results provided an overview of the Principal Leadership and Teacher Commitment effect in Effectiveness Islamic School. Key words: Principle Leadership, Teacher Commitment, Effectiveness of Islamic School